Analysis of Production and income of Walnut Snacks in the Ifamoy Home Industry, Tabona Vilage, South Ternate City - Ebit, Nursafa; La Kamisi, Haryati; Rope, Ranita; Marsaoly , Hasrul A.; Ekaria, Ekaria (Agrikan Jurnal Agribisnis Perikanan, 2025)
Walnuts are not only a mixture of food and drinks but Ifamoy Home Industry can create snacks such as fried walnuts, gulmer walnuts, roasted walnuts, himalayan roasted walnuts, krenyes walnuts and chocolate walnuts. The purpose of this study is to determine the manufacturing process and analyze the costs, receipts and income of walnut snacks. The method used is quantitative descriptive method. The results of this study are the process of making walnut snacks producing 6 flavor variants including fried walnuts, gulmer walnuts, grilled walnuts, Himalayan grilled walnuts, krenyes walnuts and chocolate walnuts. The process of making 6 flavors of walnut snacks by processing, starting from the preparation of raw materials, soaking, peeling, filtering, mixing ingredients, cooking, packaging and up to the marketing stage. The costs incurred in one production of walnut snacks amounted to Rp 4,730,334 and the revenue obtained was Rp 7,500,000, so that the total revenue earned by Ifamoy Home Industry in one production of walnut snacks amounted to Rp 2,769,656. The income earned is the income per day from the production of walnut snacks.